Guidelines for the clinical management of familial adenomatous polyposis (FAP). Issue 5 (14th January 2008) - Vasen, H F A; Möslein, G; Alonso, A; Aretz, S; Bernstein, I; Bertario, L; Blanco, I; Bülow, S; Burn, J; Capella, G; Colas, C; Engel, C; et al.
Abstract : Background: Familial adenomatous polyposis (FAP) is a well-described inherited syndrome, which is responsible for <1% of all colorectal cancer (CRC) cases. The syndrome is characterised by the development of hundreds to thousands of adenomas in the colorectum. Almost all patients will develop CRC if they are not identified and treated at an early stage. The syndrome is inherited as an autosomal dominant trait and caused by mutations in the APC gene. Recently, a second gene has been identified that also gives rise to colonic adenomatous polyposis, although the phenotype is less severe than typical FAP. The gene is the MUTYH gene and the inheritance is autosomal recessive. In April 2006 and February 2007, a workshop was organised in Mallorca by European experts on hereditary gastrointestinal cancer aiming to establish guidelines for the clinical management of FAP and to initiate collaborative studies. Thirty-one experts from nine European countries participated in these workshops. Prior to the meeting, various participants examined the most important management issues according to the latest publications. A systematic literature search using Pubmed and reference lists of retrieved articles, and manual searches of relevant articles, was performed. During the workshop, all recommendations were discussed in detail. Because most of the studies that form the basis for the recommendations were descriptive and/or retrospective in nature, many of them were based on expert opinion. The guidelines described herein may be helpful in the appropriate management of FAP families. In order to improve the care of these families further, prospective controlled studies should be undertaken.